2001
DOI: 10.1046/j.1365-2591.2001.00415.x
|View full text |Cite
|
Sign up to set email alerts
|

Alpha‐ and beta‐forms of gutta‐percha in products for root canal filling

Abstract: It was concluded that heating dental gutta-percha to 130 degrees C causes physical changes; this was not seen with chemically pure gutta-percha. The presence of additives in the dental samples altered material behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
51
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 7 publications
(7 reference statements)
2
51
0
3
Order By: Relevance
“…The results of the melting point determination for gutta-percha are consistent with other studies (16). The material tested is ␤ gutta-percha because of the typical endothermic peaks.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The results of the melting point determination for gutta-percha are consistent with other studies (16). The material tested is ␤ gutta-percha because of the typical endothermic peaks.…”
Section: Discussionsupporting
confidence: 89%
“…Thermoplastic compaction of gutta-percha is an obturating technique that has been advocated because it seals the root canal system and reduces microbial leakage (13,14). Where there have been studies addressing the thermal properties of gutta-percha, there have been no studies evaluating the thermal properties of Resilon (15,16). The purpose of this study was to compare the melting point, enthalpy change with melting, specific heat capacity and heat transfer between gutta-percha and Resilon.…”
mentioning
confidence: 99%
“…The effects of temperature changes on gutta-percha cones have been widely studied (7)(8)(9). When heated, gutta-percha changes from the beta to the alpha phase at temperatures varying between 42 C and 49 C and from the alpha phase to the amorphous form between 53 C and 59 C (9).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of temperature variations on the plastification of different types of guttapercha as a result of thermoplastification techniques depends on the physical and chemical properties of the filling material (7,8). Schilder et al (9) have shown that when gutta-percha is heated, it changes from the beta phase to the alpha phase at temperatures between 42 C and 49 C and from the alpha phase to the amorphous form at temperatures between 53 and 59 C. As an alternative to gutta-percha cones, Resilon is a synthetic polymer-based root canal filling material that contains bioactive glass, bismuth oxychloride, and barium sulfate; similar to gutta-percha, Resilon also presents thermoplastic properties (10).…”
mentioning
confidence: 99%
“…Both materials have also been shown to have the same melting point (60℃). 1,4,5 However, in the comparison of specific heat capacities of the two materials, Resilon revealed significantly more heat absorption for melting compared to gutta percha. 1 Resilon allowed deeper penetration with a spreader than gutta percha when using the same controlled pressure during compaction.…”
Section: Introductionmentioning
confidence: 99%